To the Question of Terminology, Expert Criteria for Evaluating the Effectiveness of Antiangiogenic Therapy and the Prevalence of Refractory Forms of Neovascular Age-Related Macular Degeneration. Review - V. G. Likhvantseva; V. N. Trubilin; S. G. Kapkova; A. S. Gevorgyan (Oftalʹmologiâ)
The authors presented a review of studies aimed at assessing the effectiveness of antiangiogenic therapy in patients with neovascular form of age-related macular degeneration. The purpose of this review was to clarify the prevalence of true refractory forms of WMD on literary data. The vast majority of experts consider the marker of “refractory” the exit of the dye from the vessels on fluorescent angiography (FAG), fibrovascular detachment of pigment epithelium with intraretinal and/or subretinal fluid on optical coherent tomography, an increase in hemorrhage on the eye compared to the initial level of post-loading phase therapy. The analysis showed a wide corridor of indicators, due to different approaches and timing of the assessment of the respondent’s status, as well as expert criteria for the effectiveness of antiangiogenic therapy. In addition, the authors drew attention to the different understanding of the terms tahiphylaxis and tolerance, presented by the researchers. Many papers are replacing these perceptions. The our work presents the fundamental differences of these biological phenomena in the clinic and morphometric data, as well as the timing of development. Meanwhile, overcoming resistance involves an accurate diagnosis of the pharmacological cause and a subsequent differentiated approach to solving the problem. An overview of the work on overcoming refractory to antiangiogenic drugs in various ways is presented.